New dimensions of PD-1/PD-L1 inhibitor combination therapy in cancer treatment: current advances and future perspectives - Tong, Cheng; Wu, Yue; Wu, Renzhao (Frontiers in Immunology, 2025)
The treatment of tumors remains one of the most challenging issues in modern medicine. For a long time, surgical intervention and radiochemotherapy were the primary methods employed to combat tumors; however, the therapeutic outcomes often fell short of expectations. Immunotherapy offers a promising alternative by enhancing the patient’s immune system’s ability to recognize and eliminate tumor cells while minimizing damage to normal cells and tissues. This advancement has brought new hope for cancer patients. In recent years, significant progress has been made in tumor immunotherapy with immune checkpoint inhibitors (ICIs), particularly Programmed Cell Death Protein-1 (PD-1)/Programmed Cell Death-Ligand 1 (PD-L1) inhibitors. An increasing number of researchers have discovered that combination therapy involving PD-1/PD-L1 inhibitors alongside chemotherapeutic agents or other types of ICIs yields more pronounced effects compared to monotherapy. Nevertheless, there remains a considerable risk of developing resistance and experiencing various adverse events. Traditional Chinese medicine (TCM) is frequently utilized as an adjunctive treatment for tumors due to its potential to enhance overall immune function in patients. Recent studies indicate that combining TCM with PD-1/PD-L1 inhibitors can significantly improve median survival times for patients, undoubtedly providing new directions for cancer treatment, however, there remains a lack of sufficient large-sample prospective controlled studies to provide evidence supporting the combined treatment of traditional Chinese medicine and immune checkpoint inhibitors for tumors. This study summarizes recent research on the combined use of PD-1/PD-L1 inhibitors with chemotherapeutic drugs, other ICIs, or TCM in cancer therapy. The aim is to explore their synergistic mechanisms and clinical application value while drawing greater attention from scholars to the significant value of traditional Chinese medicine in the combined treatment strategies for tumors. Additionally, this research provides insights into future prospects for anti-tumor research within TCM.